Synthesis and Characterization of Thermally Treated HKUST-1 Metal Organic Framework for Carbon Dioxide Capture - Tangavaloo, Vishantini (IRC, 2016)
HKUST-1, is one of the most expansively studied MOFs, however, synthesis method for obtaining optimum surface area for CO2 capture is yet to be reported.Thus, in the present work, thermally treated HKUST-1 was synthesized with different procedure and was further thermally treated at 160°C and 200°C from each parent sample respectively. Each procedure differs by the solvent used to synthesized HKUST-1 which are polar protic solvent; ethanol and water and polar aprotic solvents; DMF. Each sample was further characterized accordingly for surface area and morphology. For the surface area, HKUST-1 that was synthesized with polar aprotic solvents thermally treated at 200°C shows the highest surface area which is 1443.12 m2 g-1 followed by HKUST-1 which was synthesized with polar protic solvents shows 1200.93 m2 g-1 .